Evaluation of physical aspects and standards of normality of thorax radiography by medical students in faculty of Teresina-PI (Research, Society and Development, 2021)
The chest x-ray is one of the most requested imaging exams in medical practice, it is from this that it is possible to identify the main thoracic structures. However, in addition to being difficult to read, its interpretation depends on the exam operator, the technique used and the evaluator's knowledge. The research, which consists of a cross-sectional, descriptive study with a quantitative approach, was carried out using a 9-question form prepared by the authors themselves and answered by academics from the 9th to the 12th period of medicine at the UNINOVAFAPI institution, in Teresina-PI, in the year of 2021, and its main objective is to assess the knowledge of medical students about the technical parameters and normality of this imaging exam. The results showed an arithmetic mean of 6 points, which corresponded to 66.7% of the questionnaire. It was found that 71.33% of students achieved a grade equal to or higher than the average of the exam, therefore, it is concluded that the research found a satisfactory result. In the present study, the results show relevant indices in the assessment of normality parameters of chest X-rays by medical students. It is evident that teaching presents great variability between training programs in residency and medical school.